2005
DOI: 10.21273/hortsci.40.6.1682
|View full text |Cite
|
Sign up to set email alerts
|

Improving Productivity of Open-pollinated Processing Tomato Cultivars

Abstract: In contrast to developed countries open-pollinated (OP) processing tomato cultivars still have a certain market value in Turkey. A total of 26 subpopulations of 6 different OP cultivars (9 of Rio Grande, 5 of Rio Fuego, and 3 of each of C-37, Interpeel, T2 Improved, and VF 6203) were evaluated in two experimental sites in Marmara Region and Aegean Region. A high degree of phenotypic variance for yield (kg/plant) was found for most subpopulations which revealed the variation for yield amongst individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…varieties -Sankranthi, Nandi, and Vybhav -now available for cultivation in South India are resistant to tomato leaf curl virus disease. [12] This study evaluates hybrid and local Indian tomato varieties to increase tomato-resistant genes. Our research findings also showed that local or hybrid varieties were equally susceptible to bacterial wilt.…”
Section: Original Articlementioning
confidence: 99%
“…varieties -Sankranthi, Nandi, and Vybhav -now available for cultivation in South India are resistant to tomato leaf curl virus disease. [12] This study evaluates hybrid and local Indian tomato varieties to increase tomato-resistant genes. Our research findings also showed that local or hybrid varieties were equally susceptible to bacterial wilt.…”
Section: Original Articlementioning
confidence: 99%
“…Cadascun dels segments presenta els seus propis ideotips, fet que ha provocat una divergència a nivell de fons genètic entre els dos grups cultivats ; (Sim et al, 2011) Zhang et al, 2000) ha permès incrementar l'eficiència en la recol•lecció. Paral•lelament els esforços s'han centrat en millorar el contingut en sòlids solubles del fruit, la viscositat i la intensitat de color vermell (Grandillo et al, 1999b;Duman et al, 2005). La millora genètica del tomàquet destinat al consum en fresc s'ha centrat principalment en el rendiment, la conservació en postcollita, la fermesa del fruit i els aspectes relacionats amb la morfologia del fruit (Foolad, 2007).…”
Section: La Millora Genètica Modernaunclassified